Analysis of two topotecan treatment schedules in patients with recurrent ovarian cancer. (3rd March 2016) - Bruchim, Ilan; Ben-Harim, Zipi; Piura, Ettie; Haran, Gabi; Fishman, Ami
Abstract : Two topotecan treatment schedules in patients with recurrent epithelial ovarian cancer were evaluated. Protocol A (21 days) was 1.5 mg/m 2 /day topotecan on days 1 through 5 of a 21-day cycle; Protocol B (weekly) 4 mg/m 2 on days 1, 8, and 15 of a 28-day cycle. Efficacy was determined by clinical exam, CT scan, and CA125 levels. Forty-three patients on Protocol A and 21 on Protocol B were evaluated. As second-line treatment, Protocol A response was 9/20 (45%). Response to Protocol B was 4/17 (23.5%; NS). As third line or more, the response on Protocols A and B together was only 3/27 (11%). High-grade haematological toxicity was reported in 12/43 (27.9%) on Protocol A and 1/21 (4.8%) on Protocol B ( p  = 0.04). There was no difference in progression-free-intervals between schedules in second-line treatment. The weekly protocol had lower severe haematological toxicity. Clinical response in third line or more was very low.